Engineering Loyalty in the Digital Age: The Dual Impact of E-Service and Promotion in Banking - Sukardi, Sukardi; Asakdiyah, Salamatun; Ismanto, Deny; Salampessy, Andy Passyada (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
This study examines how electronic service quality and promotional strategies influence customer satisfaction and loyalty in the Indonesian banking digital ecosystem. Moving beyond linear service models, it introduces a dual-pathway framework in which both functional (e-service) and persuasive (promotion) mechanisms shape satisfaction and loyalty concurrently. Based on a purposive sample of 173 Bank Rakyat Indonesia’s digital users, findings indicate that electronic services and promotions significantly enhance satisfaction, and all three constructs—e-service, promotion, and satisfaction—positively affect customer loyalty. These results reaffirm the satisfaction–loyalty nexus, while highlighting the role of digitally mediated trust and perceived value in sustaining customer commitment. For practitioners, the study urges banks—particularly those with extensive rural reach—to modernize service infrastructures while delivering clear, customer-centered promotions. In an era where customer patience is measured in seconds, loyalty is no longer given—it must be engineered.